Pemberdayaan Masyarakat Melalui Pelatihan Dasar Pemandu Wisata Lokal Di Dusun Mendiro Desa Panglungan - Kartika, Dhian Satria Yudha; Endriana, Fathika; Halila, Azaria Ainun; Pratama, Virgiawan Yoga; Rengganis, Aidha Kiftia (CV. ITTC INDONESIA, 2023)
Community empowerment aims to increase the ability and skills independently to develop and innovate, through basic local tour guide training activities as a community empowerment program that will help the people in Dusun Mendiro know the basics of tour guides which will later be used to improve the economy of the surrounding community. However, the basic training for local tour guides held by KKN students from the East Java